PERENCANAAN STRUKTUR BANGUNAN GEDUNG HOTEL HORISON PEKALONGAN - Andy Purwanto; Muhammad Tri Prayogy; Ilham Nurhuda; Parang Sabdono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Design of highrise building includes design of structure elements such as floor slabs, stairs, beam-column frames and foundations to withstand all working loads. Therefore, an engineer should select the most appropriate structural system such as fully elastic, partially ductile or fully ductile. The structure of Horison Hotel Pekalongan is designed to apply Special Moment Resisting Frame System (SRPMK) based on Indonesia building codes and standard. The structure analysis was conducted using ETABS v.9.7.1 software. The seismic analysis using the response spectrum dynamic analysis obtained the value of maximum vibration period of 1.74 seconds and design seismic force (V) = 344.18 ton. The internal forces calculated from ETABS v.9.7.1 were used to determine the amount of reinforcement required by the structure. Results obtained from the design show that Special Moment Resisting Frame System (SRPMK) used in Horison Hotel Pekalongan is capable of supporting all working loads considered in the analysis.